ANTITUSSIVE DRUGS IN CHILDREN’S PRACTICE - N. G. KOLOSOVA; S. I. SHATALINA (Медицинский совет, 2017)
Adequate choice and use of antitussive therapy in pediatrics presupposes knowing at least the two key aspects: causes of cough and the specific mechanism of the cough reflex in children, as well as the mechanisms of action of antitussive drugs used. The need for the treatment of cough as such, that is, prescription of the so-called antitussive drugs, arises mainly in children with nonproductive, dry, persistent cough. Central antitussives suppress the function of the cough center in the medulla oblongata or other associated nerve centers of the brain. The antitussive drug butamirate, often used in children, selectively affects the cough center, does not cause respiratory depression, has an extremely low incidence of side effects, remains effective in prolonged therapy, and starts to exert its maximum effect after the first application